Impact of internal communication on employee commitment in Petronas Penapisan Melaka Sdn Bhd / Muhammad Syukree Afandi and Siti Norzahirah Yahya - Afandi, Muhammad Syukree; Yahya, Siti Norzahirah (Faculty of Business and Management, 2016)
Employee commitment is and attitude that makes the employee become motivate and increase their passionate in their work involvement. when they are passionate, they will have more energy on performing their work. Based on the observation, there are some internal factor that driver for getting the best result in term of employee commitment. The research entitles "Impact of internal communication on employee commitment in PETRONAS PENAPISAN MELAKA SDN BHD (PP (M) SB)" was conducted to evaluate the factors that affect the employee commitment among employees in PP(M)SB. Three factors have been chosen to determine the level of employee commitment which are superior-subordinate communication, superior openness and opportunity for upward communication. The research was conducted within four months time starting from February 2016 until July 2016. Two hundred (200) respondents have been given the questionnaires in order to obtain the relevant information. based on the result, it is found that only two out of three factors that have a relationship with the employee commitment. That are superior-subordinate communication and superior openness. The finding of the study could be useful for the company to realize what are factors that they need to focus in order to get more commitment from their employee.